Analisis Pengaruh Komitmen Organisasi dan Pengalaman Kerja terhadap Kinerja Karyawan (Studi PD. BPR BKK DEMAK Kantor Pusat Operasional, Kantor Cabang Wonosalam dan Kantor Cabang Karang Tengah) - Durrotul Chikmiyyah; Umar Chadhiq; Nanang Yusroni (Journal of Management and Business Review, 2021)
This article analyzes the effect of work experience and organizational commitment on the performance of PD employees. The data analysis method used is validity test, reliability test, classic assumption test. BPR BKK Demak. In simultaneous testing (test f) work experience variables and organizational commitment to the performance of PD employees. BPR BKK Demak shows f count 3.756 f table of 3.25 with a significance level of 0.048 0.05, meaning that together there is a variable influence of work experience and organizational commitment on the performance of PD employees. BPR BKK Demak. The results of testing the coefficient of determination (obtained the figure 0.140 or 14% on the variables of work experience and organizational commitment show an effect on the performance of PD employees